Georg Bredig and fellow chemists in Amsterdam (1894)
Group photograph showing chemists in Amsterdam. The pictured individuals are likely the students and colleagues of Jacobus van’t Hoff (1852-1911). Handwritten annotations identify the individuals from left to right as "Wehmann", Geertruida Wilhelmina Petronella van Maarseveen (1873-1943), Ernst J. Cohen (1869-1944), "Philipps," "Groshans," "Moor," Willem P. Jorissen, "Braskamp," Georg Bredig (1868-1944), and Viktor Rothmund (1870-1927). In 1894, Bredig traveled to Amsterdam to study physical chemistry under van’t Hoff.
Keywords: Rothmund, Viktor, 1870-1927; Hoff, J. H. van 't (Jacobus Henricus), 1852-1911; Universiteit van Amsterdam; Chemistry, Physical and theoretical; Chemists; Bredig, Georg, 1868-1944; Women chemists; Women in science